FAKTOR - FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KECAMATAN SEMARANG SELATAN - Nurul Khikmah, 11.05.52.0195; Nurhayati, Ida (Students Journal of Accounting and Banking, 2016)
This study was used to test on the influence of these factors in themselves taxpayer to the acceptance of land and building tax in the District of South Semarang. reasons for choosing districts south of Semarang, because of tax arrears in the south is quite high compared to other districts in the city of Semarang. The population in this study is an individual taxpayer residing in the district south of Semarang totaling 1,644,267 sampling is done by random sampling technique in which respondents in this research were 100 taxpayers were divided into 10 villages in the district south of Semarang so each village is 10 respondents. The results showed that awareness of taxation and understanding of the taxpayer on the tax laws, Perception sanctions and penalties affect positively and significantly to the tax revenue of the UN, while the income of the taxpayer significant negative effect on the tax revenue of the UN, and service fiskus positive effect is not significant to the success of UN tax revenue.Keywords:Â Tax Awareness, Understanding Taxpayers On Tax Law, The Perception of Sanctions and Fines, Mandatory Income Tax, Service Tax Authorities, Tax Revenue